Silicon-based negative electrode material and preparation method and application thereof
By depositing silicon and non-metal doped elements on the porous zeolite framework, a silicon-based negative electrode material with high conductivity and good electrochemical properties was prepared, which solved the problem of volume expansion of silicon-based materials during circulation. Suitable for commercial promotion.
Patent Information
- Application Number
- CN202310989190.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-14
AI Technical Summary
The silicon-based anode material has huge volume expansion during the circulation process, resulting in collapse of the electrode structure, low conductivity and poor electrochemical performance, limiting its commercial application.
Using porous zeolite as the framework structure, silicon and non-metal doped elements (such as B, P, S, N, C, As, Te) are uniformly deposited in the pores of porous zeolites, and silicon-based negative electrode materials are prepared by vapor deposition. A carbon coating is optionally added to improve electrical conductivity.
It effectively suppresses the volume expansion of silicon-based materials, improves the conductive and electrochemical properties of the materials, extends the cycle life of lithium batteries, and reduces production costs.
Smart Images

Figure CN119447212A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a silicon-based negative electrode material and a preparation method and application thereof. Background Art
[0002] At present, with the rapid development of the power battery industry, the requirements for energy density of upstream materials are getting higher and higher. Due to the low theoretical gram capacity of graphite anode, the shipment volume of silicon-based anode materials has increased significantly. In addition, silicon-based materials also have the advantages of abundant reserves, environmental friendliness, and low prices, and are regarded as one of the most promising anode materials.
[0003] However, silicon-based materials have a huge volume expansion (>300%) during the cycle process, which will cause the silicon particles to break and further lead to the pulverization of the electrode; and the huge volume expansion will cause the cracked electrode to continue to grow at the solid electrolyte interface, consuming limited lithium sources and electrolytes, causing the electrode capacity to decline rapidly. In addition, the low conductivity further limits the commercial application of silicon-based materials.
[0004] Currently, porous ceramic materials are selected as the skeleton structure and silicon or silicon iodide is deposited in the pores of the porous ceramics to prepare negative electrode materials in order to improve the problems existing in the above-mentioned silicon-based materials. However, due to the low density of porous ceramic materials, the limited mechanical stress they can withstand, their high brittleness, and the problem of structural collapse that is prone to occur, and the complex and costly process for preparing porous / fine-porous ceramic materials, their application in the preparation of negative electrode materials is still subject to certain limitations and there is a risk of failure.
[0005] Therefore, it is necessary to develop a negative electrode material that can inhibit the volume expansion of silicon-based materials while increasing conductivity and improving the electrochemical properties of negative electrode materials, and that is low in cost and suitable for commercial promotion and use. Summary of the invention
[0006] The embodiment of the present invention provides a silicon-based negative electrode material and a preparation method and application thereof, the purpose of which is to inhibit the volume expansion of the silicon-based negative electrode material during battery cycling, improve the conductivity of the material, and thus improve the electrochemical performance of the lithium battery.
[0007] To this end, in a first aspect, an embodiment of the present invention provides a silicon-based negative electrode material, the silicon-based negative electrode material comprising: a porous zeolite, and silicon and a non-metallic doping element deposited in the pores of the porous zeolite;
[0008] Wherein, the material of the non-metallic doping element includes: one or more of B, P, S, N, C, As, and Te elements;
[0009] The mass of the non-metallic doping element accounts for 0.5%-15% of the total mass of the silicon-based negative electrode material;
[0010] The mass of the silicon accounts for 50%-80% of the total mass of the silicon-based negative electrode material.
[0011] Preferably, the particle size Dv50 of the porous zeolite is between 500nm-100μm; the pore size of the porous zeolite is between 0.1nm-10μm; and the porosity of the porous zeolite is between 30%-95%.
[0012] Preferably, the silicon-based negative electrode material further includes a carbon coating layer; the mass of the carbon coating layer accounts for 0-25% of the total mass of the silicon-based negative electrode material.
[0013] In a second aspect, an embodiment of the present invention provides a method for preparing the silicon-based negative electrode material according to the first aspect, the preparation method comprising:
[0014] Step S1, preparation of porous zeolite, specifically: adding a sugar source to a mixed solution containing an aluminum source, a silicon source and a structure directing agent, stirring to solidify the mixed solution, and obtaining a dry gel after drying, and then subjecting the dry gel to a steam-assisted crystallization treatment to obtain a precursor powder, and then calcining the precursor powder in an air atmosphere to obtain a porous zeolite;
[0015] Step S2, placing the porous zeolite on a substrate in a first furnace chamber of a vapor deposition furnace, placing a material containing a non-metallic doping element in a second furnace chamber of the vapor deposition furnace; raising the temperature in the second furnace chamber of the vapor deposition furnace to 500° C.-1500° C. under a protective atmosphere to vaporize the material containing a non-metallic doping element; introducing a gas containing a silicon element into the second furnace chamber through a carrier gas to obtain a mixed gas source;
[0016] Step S3, introducing the mixed gas source into the first furnace chamber, cooling and depositing it in the pores of the porous zeolite to obtain a silicon-based negative electrode material.
[0017] Preferably, the silicon source includes one or more of ethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, and tetramethyl orthosilicate;
[0018] The aluminum source includes: one or more of aluminum triethoxide, aluminum isopropoxide, aluminum isobutoxide, and aluminum chloride;
[0019] The structure directing agent includes: one or more of polyvinyl pyrrolidone, amino resin, and tetrapropylammonium hydroxide;
[0020] The sugar source includes: one or more of sucrose, glucose, and chitosan;
[0021] The molar ratio of the silicon source, the aluminum source, water and the structure directing agent is 1:[0.02-0.05]:[15-25]:[0.02-0.1];
[0022] The molar ratio of the aluminum source to the sugar source is [1:5] to [2:1].
[0023] Preferably, the drying conditions are as follows: drying in a vacuum drying oven at 40°C to 90°C for 8 to 15 hours;
[0024] The crystallization treatment method is specifically: hydrothermally crystallizing the xerogel at a temperature in the range of 130° C. to 150° C. for 12 hours to 18 hours;
[0025] The calcination method is specifically as follows: placing the precursor powder in a high-temperature furnace, heating it to 500° C. to 700° C. in an air atmosphere, keeping the temperature for 6 to 10 hours, and the heating rate is 3 to 5° C. / min.
[0026] Preferably, the protective atmosphere is a nitrogen atmosphere or an argon atmosphere; the carrier gas is nitrogen or argon;
[0027] The silicon-containing gas includes one or more of monosilane, disilane, chlorosilane, tetrafluorosilane, hexamethyldisilane, tris(trimethylsilyl)silane, and methylvinyldichlorosilane.
[0028] Preferably, the preparation method further comprises: carbon coating the silicon-based negative electrode material;
[0029] The carbon coating method includes: one of gas phase coating, liquid phase coating or solid phase coating;
[0030] The mass of the carbon coating layer accounts for 0-25% of the total mass of the high-performance silicon-oxygen-silicon-based negative electrode material.
[0031] In a third aspect, an embodiment of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the silicon-based negative electrode material described in the first aspect.
[0032] In a fourth aspect, an embodiment of the present invention provides a lithium battery, wherein the lithium battery comprises the negative electrode plate described in the third aspect.
[0033] The purpose of the embodiment of the present invention is to provide a silicon-based negative electrode material and its preparation method and application. The silicon-based negative electrode material of the present invention is based on porous zeolite as the skeleton, and silicon and non-metallic doping elements are uniformly deposited in the pores of the porous zeolite, wherein the porous zeolite has good mechanical strength, which can buffer the stress generated by the volume expansion of silicon particles and avoid the collapse of the material structure, and the doped non-metallic elements can effectively improve the conductivity of the negative electrode material; in addition, since the porous zeolite has a large porosity and strong adsorption energy, it can more efficiently adsorb silicon and non-metallic doping elements and deposit them in its pores, thereby improving processing efficiency and deposition quality.
[0034] The silicon-based negative electrode material of the present invention is applied to lithium batteries, so that the lithium batteries can have a longer cycle life, a higher specific capacity and good conductivity.
[0035] The embodiment of the present invention provides a method for preparing a silicon-based negative electrode material. The preparation method is simple, low-cost, and applicable to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0037] Figure 1 It is a flow chart of a method for preparing a silicon-based negative electrode material provided in an embodiment of the present invention.
[0038] Figure 2 It is a schematic diagram of the structure of a silicon-based negative electrode material containing a carbon coating layer prepared in an embodiment of the present invention. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0040] An embodiment of the present invention provides a silicon-based negative electrode material, comprising: a porous zeolite, and silicon and a non-metallic doping element deposited in the pores of the porous zeolite.
[0041] Among them, the materials of non-metallic doping elements include: one or more of B, P, S, N, C, As, and Te elements; the mass of the non-metallic doping elements accounts for 0.5%-15% of the total mass of the silicon-based negative electrode material.
[0042] The silicon is silicon particles, and the mass of the silicon particles accounts for 50%-80% of the total mass of the silicon-based negative electrode material, preferably 70%.
[0043] The particle size Dv50 of the porous zeolite is between 500nm-100μm; the pore size of the porous zeolite is between 0.1nm-10μm; the porosity of the porous zeolite is between 30%-95%, preferably 75%.
[0044] In an optional solution, the silicon-based negative electrode material further includes a carbon coating layer; the mass of the carbon coating layer accounts for 0-25% of the total mass of the silicon-based negative electrode material, preferably 1%-10%.
[0045] The present invention provides a method for preparing the silicon-based negative electrode material. Figure 1 As shown, the specific steps include:
[0046] Step S1, preparation of porous zeolite, specifically: adding a sugar source to a mixed solution containing an aluminum source, a silicon source and a structure directing agent, stirring to solidify the mixed solution, and obtaining a dry gel after drying, and then subjecting the dry gel to a steam-assisted crystallization treatment to obtain a precursor powder, and then calcining the precursor powder in an air atmosphere to obtain a porous zeolite;
[0047] The silicon source includes one or more of ethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate and tetramethyl orthosilicate;
[0048] The aluminum source includes: one or more of aluminum triethoxide, aluminum isopropoxide, aluminum isobutoxide, and aluminum chloride;
[0049] The structure directing agent includes: one or more of polyvinyl pyrrolidone, amino resin, and tetrapropylammonium hydroxide;
[0050] The sugar source includes: one or more of sucrose, glucose, and chitosan;
[0051] The molar ratio of silicon source, aluminum source, water and structure directing agent is 1:[0.02-0.05]:[15-25]:[0.02-0.1];
[0052] The molar ratio of the aluminum source to the sugar source is [1:5] to [2:1];
[0053] The specific drying conditions are: drying in a vacuum drying oven at 40°C to 90°C for 8 hours to 15 hours;
[0054] The crystallization treatment method is specifically as follows: hydrothermally crystallizing the dry gel at a temperature ranging from 130° C. to 150° C. for 12 hours to 18 hours;
[0055] The calcination method is specifically as follows: placing the precursor powder in a high-temperature furnace, heating it to 500°C to 700°C in an air atmosphere, keeping it warm for 6 to 10 hours, and the heating rate is 3°C / min to 5°C / min.
[0056] Step S2, placing the porous zeolite on a substrate in a first furnace chamber of a vapor deposition furnace, placing a material containing a non-metallic doping element in a second furnace chamber of the vapor deposition furnace; raising the temperature in the second furnace chamber of the vapor deposition furnace to 500° C.-1500° C. under a protective atmosphere to vaporize the material containing a non-metallic doping element; introducing a gas containing a silicon element into the second furnace chamber through a carrier gas to obtain a mixed gas source;
[0057] The mixed gas source is a mixed gas of a gas containing a non-metallic doping element and a gas containing a silicon element; the material containing a non-metallic doping element includes: one or more of a single substance or a compound containing B, P, S, N, C, As, and Te;
[0058] The protective atmosphere is nitrogen atmosphere or argon atmosphere;
[0059] The carrier gas is nitrogen or argon, and the flow rate of the carrier gas is 0.5L / min-8L / min;
[0060] The gas containing silicon element includes: one or more of monosilane, disilane, chlorosilane, tetrafluorosilane, hexamethyldisilane, tris(trimethylsilyl)silane, and methylvinyldichlorosilane.
[0061] Step S3, introducing the mixed gas source into the first furnace chamber, cooling and depositing in the pores of the porous zeolite to obtain a silicon-based negative electrode material;
[0062] In this step, the mixed gas source is introduced into the first furnace chamber by bringing the mixed gas source into the first furnace chamber through the carrier gas.
[0063] In an optional scheme, the above preparation method also includes: carbon coating the silicon-based negative electrode material; the carbon coating method includes: one of gas phase coating, liquid phase coating or solid phase coating; the mass of the carbon coating layer accounts for 0-25% of the total mass of the high-performance silicon-oxygen-silicon-based negative electrode material, preferably 1%-10%.
[0064] In the present application, the temperature range of carbon coating is between 450℃-900℃; the applicant found that if the temperature is too low, the gas source is not completely carbonized, resulting in low utilization rate and affecting the integrity of the coating; if the temperature is too high, the silicon particles are easy to grow and break during the cycle; and it is also easy to generate inert substance silicon carbide, which affects the performance of the lithium battery.
[0065] The present application proposes that the carbon coating time is 2 hours to 5 hours; the applicant has found that if the time is shorter, the carbon content of the matrix is lower, affecting the uniformity of the coating; if the time is longer, the carbon content of the matrix is too high and the carbon layer is easily broken.
[0066] The schematic diagram of the structure of the prepared silicon-based negative electrode material containing a carbon coating layer is as follows: Figure 2 As shown, through Figure 2 It can be seen that the negative electrode material containing the carbon coating layer uses porous zeolite as a skeleton, and silicon and non-metallic elements are distributed in the pores of the porous zeolite.
[0067] The silicon-based negative electrode material prepared by the above-mentioned preparation method of the embodiment of the present invention can be used as a silicon-based negative electrode material active material for lithium battery silicon-based negative electrode material, and used to prepare a lithium battery negative electrode plate. The negative electrode plate of the present application also includes a negative electrode current collector. The present application has no special restrictions on the negative electrode current collector, as long as it can achieve the purpose of the present application, for example, it can include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil or composite current collector, etc.
[0068] In the present application, the negative electrode material of the lithium battery may further include a conductive agent. The present application has no particular limitation on the conductive agent, as long as the purpose of the present application can be achieved.
[0069] The lithium battery assembled with the negative electrode sheet prepared by the silicon-based negative electrode material of the present invention includes, but is not limited to: lithium metal secondary battery, lithium ion secondary battery, lithium polymer secondary battery or lithium ion polymer secondary battery, etc.
[0070] A lithium battery containing the silicon-based negative electrode material provided by an embodiment of the present invention, on the one hand, because the porous zeolite skeleton structure used in the silicon-based negative electrode material has certain strength and toughness, it can buffer the stress caused by the volume effect of silicon particles, avoid pulverization, and maintain the stability of the electrode structure; on the other hand, the non-metallic doping elements deposited in the pores of the porous zeolite can accelerate the conduction speed of lithium ions and improve the overall conductivity of the material. Through the coordinated effect of the above two aspects, the lithium battery can have a lower volume expansion rate, a higher specific capacity, good conductivity and cycle performance.
[0071] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the silicon-based negative electrode material of the present invention are respectively described below with multiple specific examples.
[0072] Example 1
[0073] This embodiment provides a preparation process and performance test of a silicon-based negative electrode material. The specific preparation process is as follows.
[0074] (1) Preparation of porous zeolite, specifically: adding tetraethyl orthosilicate and aluminum isopropoxide to water, stirring at room temperature, and then adding tetrapropylammonium hydroxide to obtain a mixed solution; wherein the molar ratio of tetraethyl orthosilicate, aluminum isopropoxide, water and tetrapropylammonium hydroxide is 1:0.02:15:0.02; after the mixed solution is continuously stirred for 3 hours, sucrose is added to the mixed solution, wherein the molar ratio of aluminum isopropoxide to sucrose is 1:5, and the mixed solution is continuously stirred to solidify, and then placed in a vacuum drying oven at 60° C. for 12 hours to obtain a dry gel; Then, water is injected into the bottom of a polytetrafluoroethylene container containing a metal support, and the dried dry gel is placed in a crucible and placed on the metal support, and then placed in a reactor, and subjected to steam-assisted crystallization treatment at 140°C for 12 hours to obtain a precursor powder; the precursor powder is placed in a tubular furnace, and heated to 600°C at a heating rate of 3°C / min in an air atmosphere, and a porous zeolite is obtained after being kept warm for 6 hours; wherein the particle size Dv50 of the obtained porous zeolite is 500nm, the pore size distribution of the pores is between 20nm-80nm, and the porosity is 95%.
[0075] (2) Take 1 kg of the porous zeolite prepared as above and place it on a substrate in the first furnace chamber of a vapor deposition furnace, and place 200 g of carbon black in the second furnace chamber of the vapor deposition furnace; under a nitrogen atmosphere, raise the temperature in the second furnace chamber of the vapor deposition furnace to 500°C to vaporize the carbon black; introduce monosilane into the second furnace chamber through nitrogen at a flow rate of 3 L / min to obtain a mixed gas source.
[0076] (3) The mixed gas source is introduced into the first furnace chamber through nitrogen at a flow rate of 3 L / min, cooled and deposited in the pores of the porous zeolite, thereby obtaining a silicon-based negative electrode material with Si and C deposited in the pores.
[0077] The silicon-based negative electrode material prepared in this embodiment is carbon-coated, specifically: 1 kg of silicon-based negative electrode material is placed in a rotary kiln, the temperature is raised to 800°C under an argon atmosphere, argon gas and acetylene gas are introduced at a volume ratio of 3:1 for gas phase coating, the gas source is turned off after keeping warm for 100 minutes, and the material is discharged and classified after cooling to room temperature to obtain a silicon-based negative electrode material containing a carbon coating layer.
[0078] The silicon-based negative electrode material containing a carbon coating layer prepared in this embodiment was used to prepare negative electrode plates, and button-type half-cells and full cells were assembled for testing. The specific process is as follows.
[0079] The preparation method of the button half-cell is as follows: the silicon-based negative electrode material containing a carbon coating layer, the conductive additive carbon black, and the adhesive (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) are weighed according to a mass ratio of 95%:2%:3%, and the slurry is prepared with a beater, and then coated, dried, and cut into pieces, and assembled into a button half-cell in a glove box.
[0080] The button half-cell was assembled in a glove box filled with argon atmosphere, using metallic lithium as the counter electrode and a solution of 1 mol of LiPF6 in ethylene carbonate (EC) / diethyl carbonate (DEC) (v:v=1:1) as the electrolyte to assemble the half-cell. The constant current charge and discharge mode test was carried out using a charge and discharge instrument, with a discharge cut-off voltage of 0.005V and a charge cut-off voltage of 2V. The first week of charge and discharge test was carried out at a current density of C / 10.
[0081] The initial efficiency and reversible capacity test data of the button cell prepared in this example are shown in Table 1.
[0082] The preparation method of the full battery is as follows: Preparation of the negative electrode sheet: a silicon-based negative electrode material containing a carbon coating layer is configured with graphite to form a composite with a specific capacity of 450mAg / h, and a conductive additive and a binder are weighed and mixed in a ratio of 95%:2%:3%; at room temperature, the mixed material and solvent deionized water are put into a pulper to prepare a slurry; the prepared slurry is evenly coated on a copper foil, and the negative electrode sheet is obtained after drying.
[0083] Preparation of positive electrode sheet: nickel cobalt lithium manganese oxide (NMC) ternary positive electrode material, conductive agent and binder are weighed and mixed in a ratio of 96%:2%:2%; at room temperature, the mixed material and solvent N-methylpyrrolidone are put into a beater to prepare slurry; the prepared slurry is evenly coated on aluminum foil, and the positive electrode sheet is obtained after drying.
[0084] Preparation of the battery: The positive electrode of the positive electrode sheet uses an aluminum tab as an exposed tab, and the negative electrode of the negative electrode sheet uses a copper-plated nickel tab as an exposed tab. The prepared positive and negative electrode sheets and the separator are wound into a naked battery cell, and then the battery cell is packaged with an aluminum-plastic film through a high-frequency sealing process. The battery is vacuum-baked at high temperature to remove moisture from the battery, and then 1 mole of electrolyte is injected. The electrolyte is a mixed solution of LiPF6 and ethylene carbonate EC / dimethyl carbonate DMC (the volume ratio of EC to DMC is 1:1) to make a battery cell. After vacuum sealing, a battery is prepared.
[0085] Test: Use a charge and discharge instrument to perform constant current charge and discharge mode tests, with a discharge cut-off voltage of 2.75V and a charge cut-off voltage of 4.2V. The charge and discharge tests are all performed at a current density of 2C.
[0086] At 2C, when the battery was fully charged for 200 cycles and 400 cycles, 5 groups of batteries were dismantled, and their negative pole pieces were taken out. The thickness of 10 different areas of each pole piece was measured with a thickness gauge, and the average value was taken. Under the same test conditions, the average thickness of the pole piece in the initial state was obtained.
[0087] The calculation formula is: Full-charge expansion rate of the pole piece = (average thickness of the pole piece when fully charged with different turns - initial average thickness of the pole piece) / initial average thickness of the pole piece.
[0088] The test results of the expansion rate of the negative electrode sheet of the full battery prepared in this embodiment at 200 and 400 cycles at a 2C rate, as well as the cycle capacity retention rate data after 400 cycles, are detailed in Table 1.
[0089] Example 2
[0090] This embodiment provides a preparation process and performance test of a silicon-based negative electrode material. The specific preparation process is as follows.
[0091] (1) Preparation of porous zeolite, specifically: adding tetramethyl orthosilicate and aluminum nitrate to water, stirring at room temperature, and then adding polyvinyl pyrrolidone to obtain a mixed solution; wherein the molar ratio of tetramethyl orthosilicate, aluminum nitrate, water and polyvinyl pyrrolidone is 1:0.03:18:0.04; after the mixed solution is continuously stirred for 3 hours, glucose is added to the mixed solution, wherein the molar ratio of aluminum nitrate to glucose is 1:4, and the mixed solution is continuously stirred to solidify, and then placed in a vacuum drying oven at 50° C. for 10 hours to obtain a dry gel; Then, water is injected into the bottom of a polytetrafluoroethylene container containing a metal support, the dried dry gel is put into a crucible and placed on the metal support, placed in a reactor, and subjected to steam-assisted crystallization treatment at 130°C for 12 hours to obtain a precursor powder; the precursor powder is placed in a tubular furnace, and the temperature is increased to 500°C at a heating rate of 3°C / min in an air atmosphere, and the porous zeolite is obtained after being kept warm for 7 hours; wherein the particle size Dv50 of the obtained porous zeolite is 800nm, the pore size distribution of the pores is between 80nm-160nm, and the porosity is 90%.
[0092] (2) Take 900 g of the porous zeolite prepared as above and place it on a substrate in the first furnace chamber of a vapor deposition furnace, and place 250 g of sulfur powder in the second furnace chamber of the vapor deposition furnace; under a nitrogen atmosphere, raise the temperature in the second furnace chamber of the vapor deposition furnace to 500°C to vaporize the sulfur powder; introduce disilane into the second furnace chamber through nitrogen at a flow rate of 2 L / min to obtain a mixed gas source.
[0093] (3) The mixed gas source is introduced into the first furnace chamber through nitrogen at a flow rate of 3 L / min, cooled and deposited in the pores of the porous zeolite, thereby obtaining a silicon-based negative electrode material with Si and S deposited in the pores.
[0094] The silicon-based negative electrode material prepared in this embodiment is carbon-coated, specifically: 900g of silicon-based negative electrode material is placed in a rotary kiln, the temperature is raised to 800°C under an argon atmosphere, argon and propane gas are introduced at a volume ratio of 3:2 for gas phase coating, the gas source is turned off after keeping warm for 95 minutes, and the material is discharged and classified after cooling to room temperature to obtain a silicon-based negative electrode material containing a carbon coating layer.
[0095] The silicon-based negative electrode material containing a carbon coating layer prepared in this embodiment is used to prepare negative electrode plates, and button-type half-cells and full cells are assembled for testing. The assembly and testing methods are the same as in Example 1.
[0096] The initial efficiency and reversible capacity test data of the button cell prepared in this embodiment are shown in Table 1; the test results of the expansion rate of the negative electrode plate of the full battery at 2C rate for 200 and 400 cycles, as well as the cycle capacity retention rate data after 400 cycles, are shown in Table 1.
[0097] Example 3
[0098] This embodiment provides a preparation process and performance test of a silicon-based negative electrode material. The specific preparation process is as follows.
[0099] (1) Preparation of porous zeolite, specifically: adding tetrabutyl orthosilicate and aluminum isobutoxide to water, stirring at room temperature, and then adding amino resin to obtain a mixed solution; wherein the molar ratio of tetrabutyl orthosilicate, aluminum isobutoxide, water and amino resin is 1:0.04:17:0.05; after the mixed solution is continuously stirred for 3 hours, chitosan is added to the mixed solution, wherein the molar ratio of aluminum isobutoxide to chitosan is 1:3, and the mixed solution is continuously stirred to solidify, and then placed in a vacuum drying oven at 70°C for 8 hours to obtain a dry gel; and then Water is injected into the bottom of a polytetrafluoroethylene container containing a metal support, the dried dry gel is loaded into a crucible and placed on the metal support, and then placed in a reactor, and subjected to steam-assisted crystallization treatment at 150°C for 9 hours to obtain a precursor powder; the precursor powder is placed in a tubular furnace, and heated to 700°C at a heating rate of 3°C / min in an air atmosphere, and the porous zeolite is obtained after being kept warm for 7 hours; wherein the particle size Dv50 of the obtained porous zeolite is 900nm, the pore size distribution of the pores is between 100nm and 300nm, and the porosity is 85%.
[0100] (2) Take 800g of the porous zeolite prepared as above and place it on a substrate in the first furnace chamber of a vapor deposition furnace, and place 240g of black phosphorus in the second furnace chamber of the vapor deposition furnace; under a nitrogen atmosphere, raise the temperature in the second furnace chamber of the vapor deposition furnace to 600°C to vaporize the black phosphorus; introduce tetrafluorosilane into the second furnace chamber through nitrogen at a flow rate of 2L / min to obtain a mixed gas source.
[0101] (3) The mixed gas source is introduced into the first furnace chamber through nitrogen at a flow rate of 3 L / min, cooled and deposited in the pores of the porous zeolite, thereby obtaining a silicon-based negative electrode material with Si and P deposited in the pores.
[0102] The silicon-based negative electrode material prepared in this embodiment is carbon-coated, specifically: 800g of silicon-based negative electrode material and asphalt emulsion are mixed in a mass ratio of 20:1, stirred for 12 hours to form a uniform slurry, the slurry is dried and placed in a rotary kiln, heated to 950°C under a nitrogen atmosphere and kept warm for 80 minutes, cooled, discharged and classified, to obtain a silicon-based negative electrode material containing a carbon coating layer.
[0103] The silicon-based negative electrode material containing a carbon coating layer prepared in this embodiment is used to prepare negative electrode plates, and button-type half-cells and full cells are assembled for testing. The assembly and testing methods are the same as in Example 1.
[0104] The initial efficiency and reversible capacity test data of the button cell prepared in this embodiment are shown in Table 1; the test results of the expansion rate of the negative electrode plate of the full battery at 2C rate for 200 and 400 cycles, as well as the cycle capacity retention rate data after 400 cycles, are shown in Table 1.
[0105] Example 4
[0106] This embodiment provides a preparation process and performance test of a silicon-based negative electrode material. The specific preparation process is as follows.
[0107] (1) Preparation of porous zeolite, specifically: adding tetrapropyl orthosilicate and aluminum chloride into water, stirring at room temperature, and then adding tetrapropylammonium hydroxide to obtain a mixed solution; wherein the molar ratio of tetrapropyl orthosilicate, aluminum chloride, water and tetrapropylammonium hydroxide is 1:0.03:18:0.04; after the mixed solution is continuously stirred for 3 hours, sucrose is added into the mixed solution, wherein the molar ratio of aluminum chloride to sucrose is 1:2, and the mixed solution is continuously stirred to solidify, and then placed in a vacuum drying oven at 80°C for 8 hours to obtain a dry gel; and then Water is injected into the bottom of a polytetrafluoroethylene container containing a metal support, the dried dry gel is loaded into a crucible and placed on the metal support, and then placed in a reactor, and subjected to steam-assisted crystallization treatment at 140°C for 9 hours to obtain a precursor powder; the precursor powder is placed in a tubular furnace, heated to 700°C at a heating rate of 3°C / min in an air atmosphere, and calcined for 8 hours to obtain a porous zeolite; wherein the obtained porous zeolite has a particle size Dv50 of 13 μm, a pore size distribution of pores between 500nm and 800nm, and a porosity of 78%.
[0108] (2) Take 1.2 kg of the porous zeolite prepared as above and place it on a substrate in the first furnace chamber of a vapor deposition furnace, and place 280 g of selenium chloride in the second furnace chamber of the vapor deposition furnace; under an argon atmosphere, raise the temperature in the second furnace chamber of the vapor deposition furnace to 700°C to vaporize the selenium chloride; introduce monosilane into the second furnace chamber through argon gas at a flow rate of 1 L / min to obtain a mixed gas source.
[0109] (3) The mixed gas source is introduced into the first furnace chamber through argon gas at a flow rate of 1 L / min, cooled and deposited in the pores of the porous zeolite, thereby obtaining a silicon-based negative electrode material with Si and Se deposited in the pores.
[0110] The silicon-based negative electrode material prepared in this embodiment is carbon coated, specifically: 1 kg of silicon-based negative electrode material and graphene are dissolved in ethanol at a ratio of 18:1, and stirred for 6 hours to make the slurry uniform. The slurry is then dried, placed in a rotary kiln, heated to 900°C in a protective atmosphere, kept warm for 1 hour, cooled to room temperature, and then discharged and classified to obtain a silicon-based negative electrode material containing a carbon coating layer.
[0111] The silicon-based negative electrode material containing a carbon coating layer prepared in this embodiment is used to prepare negative electrode plates, and button-type half-cells and full cells are assembled for testing. The assembly and testing methods are the same as in Example 1.
[0112] The initial efficiency and reversible capacity test data of the button cell prepared in this embodiment are shown in Table 1; the test results of the expansion rate of the negative electrode plate of the full battery at 2C rate for 200 and 400 cycles, as well as the cycle capacity retention rate data after 400 cycles, are shown in Table 1.
[0113] Example 5
[0114] This embodiment provides a preparation process and performance test of a silicon-based negative electrode material. The specific preparation process is as follows.
[0115] (1) Preparation of porous zeolite, specifically: adding tetraethyl orthosilicate and aluminum nitrate to water, stirring at room temperature, and then adding polyvinyl pyrrolidone to obtain a mixed solution; wherein the molar ratio of tetraethyl orthosilicate, aluminum nitrate, water and polyvinyl pyrrolidone is 1:0.05:20:0.04; after the mixed solution is stirred for 3 hours, sucrose is added to the mixed solution, wherein the molar ratio of aluminum nitrate to sucrose is 1:1, and the stirring is continued to solidify the mixed solution, and then the mixed solution is placed in a vacuum drying oven at 80°C for 8 hours to obtain a dry gel; and then Water is injected into the bottom of a polytetrafluoroethylene container containing a metal support, the dried dry gel is loaded into a crucible and placed on the metal support, placed in a reactor, and subjected to steam-assisted crystallization treatment at 130°C for 9 hours to obtain a precursor powder; the precursor powder is placed in a tubular furnace, heated to 700°C at a heating rate of 3°C / min in an air atmosphere, and calcined for 10 hours to obtain a porous zeolite; wherein the obtained porous zeolite has a particle size Dv50 of 25μm, a pore size distribution of pores between 1μm and 5μm, and a porosity of 84%.
[0116] (2) Take 1 kg of the porous zeolite prepared as above and place it on a substrate in the first furnace chamber of a vapor deposition furnace, and place 350 g of melamine in the second furnace chamber of the vapor deposition furnace; under a nitrogen atmosphere, raise the temperature in the second furnace chamber of the vapor deposition furnace to 1000°C to vaporize the melamine; introduce monosilane into the second furnace chamber through nitrogen at a flow rate of 2 L / min to obtain a mixed gas source.
[0117] (3) The mixed gas source is introduced into the first furnace chamber through nitrogen at a flow rate of 2 L / min, and is cooled and deposited in the pores of the porous zeolite to obtain a silicon-based negative electrode material with Si, C, and N deposited in the pores.
[0118] The silicon-based negative electrode material prepared in this embodiment is used to prepare negative electrode plates and assemble button-type half-cells and full cells for testing. The assembly and testing methods are the same as those in Example 1.
[0119] The initial efficiency and reversible capacity test data of the button cell prepared in this embodiment are shown in Table 1; the test results of the expansion rate of the negative electrode plate of the full battery at 2C rate for 200 and 400 cycles, as well as the cycle capacity retention rate data after 400 cycles, are shown in Table 1.
[0120] Example 6
[0121] This embodiment provides a preparation process and performance test of a silicon-based negative electrode material. The specific preparation process is as follows.
[0122] (1) Preparation of porous zeolite, specifically: adding methyl orthosilicate and aluminum nitrate to water, stirring at room temperature, and then adding amino resin to obtain a mixed solution; wherein the molar ratio of methyl orthosilicate, aluminum nitrate, water and amino resin is 1:0.05:25:0.05; after the mixed solution is continuously stirred for 4 hours, chitosan is added to the mixed solution, wherein the molar ratio of aluminum nitrate to chitosan is 2:1, and the mixed solution is continuously stirred to solidify, and then placed in a vacuum drying oven at 80° C. for 10 hours to obtain a dry gel; and then Water is injected into the bottom of a polytetrafluoroethylene container containing a metal support, the dried dry gel is loaded into a crucible and placed on the metal support, and then placed in a reactor, and subjected to steam-assisted crystallization treatment at 130°C for 9 hours to obtain a precursor powder; the precursor powder is placed in a tubular furnace, and heated to 800°C at a heating rate of 3°C / min in an air atmosphere, and then kept warm for 9 hours to obtain a porous zeolite; wherein the particle size Dv50 of the obtained porous zeolite is 65μm, the pore size distribution of the pores is between 6μm and 10μm, and the porosity is 88%.
[0123] (2) Take 1 kg of the porous zeolite prepared as above and place it on a substrate in the first furnace chamber of a vapor deposition furnace, and place 280 g of asphalt in the second furnace chamber of the vapor deposition furnace; under a nitrogen atmosphere, raise the temperature in the second furnace chamber of the vapor deposition furnace to 1050°C to vaporize the asphalt; introduce methylvinyldichlorosilane into the second furnace chamber through nitrogen at a flow rate of 3 L / min to obtain a mixed gas source.
[0124] (3) The mixed gas source is introduced into the first furnace chamber through nitrogen at a flow rate of 3 L / min, cooled and deposited in the pores of the porous zeolite, thereby obtaining a silicon-based negative electrode material with Si and C deposited in the pores.
[0125] The silicon-based negative electrode material prepared in this embodiment is carbon-coated, specifically: 1 kg of silicon-based negative electrode material is placed in a rotary kiln, the temperature is raised to 900°C under an argon atmosphere, and argon gas and a mixed gas of natural gas and ethylene are introduced at a volume ratio of 2:1 for gas phase coating, wherein the volume ratio of natural gas to ethylene is 1:1, and the gas source is turned off after keeping warm for 85 minutes. After cooling to room temperature, the material is discharged and classified to obtain a silicon-based negative electrode material containing a carbon coating layer.
[0126] The silicon-based negative electrode material containing a carbon coating layer prepared in this embodiment is used to prepare negative electrode plates, and button-type half-cells and full cells are assembled for testing. The assembly and testing methods are the same as in Example 1.
[0127] The initial efficiency and reversible capacity test data of the button cell prepared in this embodiment are shown in Table 1; the test results of the expansion rate of the negative electrode plate of the full battery at 2C rate for 200 and 400 cycles, as well as the cycle capacity retention rate data after 400 cycles, are shown in Table 1.
[0128] Example 7
[0129] This embodiment provides a preparation process and performance test of a silicon-based negative electrode material. The specific preparation process is as follows.
[0130] (1) Preparation of porous zeolite, specifically: adding tetrapropyl orthosilicate and aluminum chloride into water, stirring at room temperature, and then adding amino resin to obtain a mixed solution; wherein the molar ratio of tetrapropyl orthosilicate, aluminum chloride, water and amino resin is 1:0.05:20:0.02; after the mixed solution is continuously stirred for 4 hours, chitosan is added into the mixed solution, wherein the molar ratio of aluminum chloride to chitosan is 2:1, and the mixed solution is continuously stirred to solidify, and then placed in a vacuum drying oven at 80° C. for 10 hours to obtain a dry gel; and then Water is injected into the bottom of a polytetrafluoroethylene container containing a metal support, the dried dry gel is loaded into a crucible and placed on the metal support, and then placed in a reactor, and subjected to steam-assisted crystallization treatment at 130°C for 9 hours to obtain a precursor powder; the precursor powder is placed in a tubular furnace, and heated to 800°C at a heating rate of 3°C / min in an air atmosphere, and the porous zeolite is obtained after being kept warm for 9 hours; wherein the particle size Dv50 of the obtained porous zeolite is 900nm, the pore size distribution of the pores is between 200nm and 600nm, and the porosity is 92%.
[0131] (2) Take 1 kg of the porous zeolite prepared as above and place it on a substrate in the first furnace chamber of a vapor deposition furnace, and place 320 g of red phosphorus in the second furnace chamber of the vapor deposition furnace; under a nitrogen atmosphere, raise the temperature in the second furnace chamber of the vapor deposition furnace to 1000°C to vaporize the red phosphorus; introduce disilane into the second furnace chamber through nitrogen at a flow rate of 3 L / min to obtain a mixed gas source.
[0132] (3) The mixed gas source is introduced into the first furnace chamber through nitrogen at a flow rate of 3 L / min, cooled and deposited in the pores of the porous zeolite, thereby obtaining a silicon-based negative electrode material with Si and P deposited in the pores.
[0133] The silicon-based negative electrode material prepared in this embodiment is carbon-coated, specifically: 1 kg of silicon-based negative electrode material is mixed with petroleum asphalt in a mass ratio of 15:1, placed in a rotary kiln, kept at 950°C for 120 minutes under a protective atmosphere, cooled to room temperature, and then discharged and classified to obtain a silicon-based negative electrode material containing a carbon coating layer.
[0134] The silicon-based negative electrode material containing a carbon coating layer prepared in this embodiment is used to prepare negative electrode plates, and button-type half-cells and full cells are assembled for testing. The assembly and testing methods are the same as in Example 1.
[0135] The initial efficiency and reversible capacity test data of the button cell prepared in this embodiment are shown in Table 1; the test results of the expansion rate of the negative electrode plate of the full battery at 2C rate for 200 and 400 cycles, as well as the cycle capacity retention rate data after 400 cycles, are shown in Table 1.
[0136] In order to better illustrate the effects of the embodiments of the present invention, comparative examples 1-2 are compared with the above embodiments.
[0137] Comparative Example 1
[0138] This comparative example provides a preparation process and performance test of silicon-carbon negative electrode material prepared by a traditional spray drying method. The specific preparation process is as follows:
[0139] Silicon particles, a carbon source precursor, graphite and an antioxidant in a mass ratio of 50%:25%:24%:1% were weighed, dissolved in ethanol, sand-milled to obtain a dispersion, and the dispersion was spray-dried to obtain a silicon-carbon composite material.
[0140] The prepared silicon-carbon composite material is carbon-coated, specifically: 1 kg of the silicon-carbon composite material is placed in a rotary kiln, the temperature is raised to 950°C under an argon atmosphere, argon and acetylene gas are introduced at a volume ratio of 3:1 for gas phase coating, the gas source is turned off after the temperature is kept warm for 2 hours, and the material is discharged and classified after cooling to room temperature to obtain a silicon-carbon composite material containing a carbon coating layer.
[0141] The silicon-carbon negative electrode material containing a carbon coating layer prepared in this comparative example was used to make negative electrode plates and assembled into button-type half-cells and full-cells for testing. The assembly and testing methods were the same as those in Example 1.
[0142] The initial efficiency and reversible capacity test data of the button cell prepared in this comparative example are shown in Table 1; the test results of the expansion rate of the negative electrode plate of the full battery at 2C rate for 200 and 400 cycles, as well as the cycle capacity retention rate data after 400 cycles, are shown in Table 1.
[0143] Comparative Example 2
[0144] This comparative example prepares a negative electrode material. The difference from Example 1 is that this comparative example uses porous ceramic (porous SiC) as the skeleton structure, and the vapor deposition process is the same as that of Example 1, as follows:
[0145] (1) 1 kg of porous SiC was placed on a substrate in the first furnace chamber of a vapor deposition furnace, and 200 g of carbon black was placed in the second furnace chamber of the vapor deposition furnace; under a nitrogen atmosphere, the temperature in the second furnace chamber of the vapor deposition furnace was raised to 500° C. to gasify the carbon black; monosilane was introduced into the second furnace chamber by nitrogen at a flow rate of 3 L / min to obtain a mixed gas source.
[0146] (2) The mixed gas source is introduced into the first furnace chamber through nitrogen at a flow rate of 3 L / min, cooled and deposited in the pores of the porous zeolite, thereby obtaining a negative electrode material with Si and C deposited in the pores.
[0147] (3) The negative electrode material prepared in this example is carbon-coated, specifically: 1 kg of the negative electrode material is placed in a rotary kiln, the temperature is raised to 800° C. under an argon atmosphere, argon and acetylene gas are introduced at a volume ratio of 3:1 for gas phase coating, the gas source is turned off after keeping the temperature for 100 minutes, and the material is discharged and classified after cooling to room temperature to obtain a negative electrode material containing a carbon coating layer.
[0148] The negative electrode material containing the carbon coating layer prepared in this comparative example was used to make negative electrode plates, and button-type half-cells and full-cells were assembled for testing. The assembly and testing methods were the same as those in Example 1.
[0149] The initial efficiency and reversible capacity test data of the button cell prepared in this comparative example are shown in Table 1; the test results of the expansion rate of the negative electrode plate of the full battery at 2C rate for 200 and 400 cycles, as well as the cycle capacity retention rate data after 400 cycles, are shown in Table 1.
[0150] Table 1 is a summary of the test data of the batteries assembled in Examples 1-7 and Comparative Examples 1-2:
[0151]
[0152]
[0153] From the comparison of the test data in Table 1, it can be seen that under the same test conditions, the expansion rate of the negative electrode sheets prepared in Examples 1-7 is much smaller than that in Comparative Example 1, and is also smaller than that in Comparative Example 2. This is because silicon and non-metallic doping elements are deposited in the pores of the porous zeolite by silane chemical vapor deposition. The skeleton structure of the porous zeolite has certain strength and toughness, which can buffer the stress caused by the volume effect of silicon particles, avoid pulverization, and maintain the stability of the electrode structure. In addition, from the comparison of the test data in Table 1, it can be seen that the capacity retention rate of the batteries prepared in Examples 1-7 after 400 cycles is higher than that of Comparative Examples 1-2. On the one hand, this is because the porous zeolite has a stable electrode structure; on the other hand, the doping of non-metallic elements can accelerate the conduction speed of lithium ions and improve the conductivity of the overall material, so that the battery has a good cycle life.
[0154] The purpose of the embodiment of the present invention is to provide a silicon-based negative electrode material and its preparation method and application. The silicon-based negative electrode material of the present invention is based on porous zeolite as the skeleton, and silicon and non-metallic doping elements are uniformly deposited in the pores of the porous zeolite, wherein the porous zeolite has good mechanical strength, which can buffer the stress generated by the volume expansion of silicon particles and avoid the collapse of the material structure, and the doped non-metallic elements can effectively improve the conductivity of the negative electrode material; in addition, since the porous zeolite has a large porosity and strong adsorption energy, it can more efficiently adsorb silicon and non-metallic doping elements and deposit them in its pores, thereby improving processing efficiency and deposition quality.
[0155] The silicon-based negative electrode material of the present invention is applied to lithium batteries, so that the lithium batteries can have a longer cycle life, a higher specific capacity and good conductivity.
[0156] The embodiment of the present invention provides a method for preparing a silicon-based negative electrode material. The preparation method is simple, low-cost, and applicable to large-scale production.
[0157] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A silicon-based negative electrode material, characterized in that: The silicon-based negative electrode material comprises: porous zeolite, and silicon and non-metallic doping elements deposited in the pores of the porous zeolite; Wherein, the material of the non-metallic doping element includes: one or more of B, P, S, N, C, As, and Te elements; The mass of the non-metallic doping element accounts for 0.5%-15% of the total mass of the silicon-based negative electrode material; The mass of the silicon accounts for 50%-80% of the total mass of the silicon-based negative electrode material.
2. The silicon-based negative electrode material according to claim 1, characterized in that: The particle size Dv50 of the porous zeolite is between 500nm and 100μm; the pore size of the porous zeolite is between 0.1nm and 10μm; and the porosity of the porous zeolite is between 30% and 95%.
3. The silicon-based negative electrode material according to claim 1, characterized in that: The silicon-based negative electrode material further includes a carbon coating layer; the mass of the carbon coating layer accounts for 0-25% of the total mass of the silicon-based negative electrode material.
4. A method for preparing the silicon-based negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, preparation of porous zeolite, specifically: adding a sugar source to a mixed solution containing an aluminum source, a silicon source and a structure directing agent, stirring to solidify the mixed solution, and obtaining a dry gel after drying, and then subjecting the dry gel to a steam-assisted crystallization treatment to obtain a precursor powder, and then calcining the precursor powder in an air atmosphere to obtain a porous zeolite; Step S2, placing the porous zeolite on a substrate in a first furnace chamber of a vapor deposition furnace, placing a material containing a non-metallic doping element in a second furnace chamber of the vapor deposition furnace; raising the temperature in the second furnace chamber of the vapor deposition furnace to 500° C.-1500° C. under a protective atmosphere to vaporize the material containing a non-metallic doping element; introducing a gas containing a silicon element into the second furnace chamber through a carrier gas to obtain a mixed gas source; Step S3, introducing the mixed gas source into the first furnace chamber, cooling and depositing it in the pores of the porous zeolite to obtain a silicon-based negative electrode material.
5. The preparation method according to claim 4, characterized in that: The silicon source includes one or more of ethyl orthosilicate, tetrapropyl orthosilicate, tetrabutyl orthosilicate, and tetramethyl orthosilicate; The aluminum source includes: one or more of aluminum triethoxide, aluminum isopropoxide, aluminum isobutoxide, and aluminum chloride; The structure directing agent includes: one or more of polyvinyl pyrrolidone, amino resin, and tetrapropylammonium hydroxide; The sugar source includes: one or more of sucrose, glucose, and chitosan; The molar ratio of the silicon source, the aluminum source, water and the structure directing agent is 1:[0.02-0.05]:[15-25]:[0.02-0.1]; The molar ratio of the aluminum source to the sugar source is [1:5] to [2:1].
6. The preparation method according to claim 4, characterized in that: The drying conditions are as follows: drying in a vacuum drying oven at 40°C to 90°C for 8 to 15 hours; The crystallization treatment method is specifically: hydrothermally crystallizing the xerogel at a temperature in the range of 130° C. to 150° C. for 12 hours to 18 hours; The calcination method is specifically as follows: placing the precursor powder in a high-temperature furnace, heating it to 500° C. to 700° C. in an air atmosphere, keeping the temperature for 6 to 10 hours, and the heating rate is 3 to 5° C. / min.
7. The preparation method according to claim 4, characterized in that: The protective atmosphere is a nitrogen atmosphere or an argon atmosphere; the carrier gas is nitrogen or argon; The silicon-containing gas includes one or more of monosilane, disilane, chlorosilane, tetrafluorosilane, hexamethyldisilane, tris(trimethylsilyl)silane, and methylvinyldichlorosilane.
8. The preparation method according to claim 4, characterized in that: The preparation method further comprises: carbon coating the silicon-based negative electrode material; The carbon coating method includes: one of gas phase coating, liquid phase coating or solid phase coating; The mass of the carbon coating layer accounts for 0-25% of the total mass of the high-performance silicon-oxygen-silicon-based negative electrode material.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the silicon-based negative electrode material described in any one of claims 1 to 3.
10. A lithium battery, characterized in that: The lithium battery comprises the negative electrode sheet as described in claim 9 above.
Citation Information
Cited By
Silicon-carbon composite material and preparation method thereof, secondary battery and electronic equipment
CN120958598A
Silicon-carbon composite material, preparation method therefor, secondary battery and electronic device
WO2026199228A1